Jaranan Ethnopedagogy: A Review of the Value of Christian Education from the Meaning of the Javanese Local Movement - Reni Dannari; Syani Bombongan Rantesalu (Harati: Jurnal Pendidikan Kristen, 2026)
Jaranan is a traditional Indonesian dance that contains magical elements and involves dancers performing dangerous acts. The purpose of this study is to examine the value of Christian religious education within the context of the local Javanese movement, Jaranan. This study investigates the values ​​of Christian religious education manifested in Jaranan art as an integral part of the local movement in Java. Using qualitative methods with an ethnopedagogical approach, data were collected through observation, in-depth interviews with key informants, and literature review. The results indicate that Jaranan embodies fundamental values ​​such as solidarity, social justice, and spirituality, which have significant relevance to Christian religious education. This research is expected to make a substantive contribution to the development of a contextual and transformative model of Christian religious education within the framework of the local movement.